2018
DOI: 10.3382/ps/pey178
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and biological characterization of mesenchymal stem cells from goose dermis

Abstract: The skin is a natural target of stem cell research because of its large size and easy accessibility. Cutaneous mesenchymal stem cells have shown to be a promising source of various adult stem cell or progenitor cell populations, which provide an important source of stem cell-based investigation. Nowadays, much work has been done on dermal-derived mesenchymal stem cells (DMSCs) from humans, mice, sheep, and other mammals, but the literature on avian species has been rarely reported. As an animal model, the goos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In this work, we differentiated TDSCs from blackbirds in vitro under the action of specific induction factors into osteogenic, adipogenic, and chondrogenic lineages. The differentiation was assessed using specific staining procedures, i.e., Alizarin Red S staining, Oil Red O staining, and Alcian Blue staining, respectively, as validated in other MSCs models of avian origin [ 12 , 28 , 29 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we differentiated TDSCs from blackbirds in vitro under the action of specific induction factors into osteogenic, adipogenic, and chondrogenic lineages. The differentiation was assessed using specific staining procedures, i.e., Alizarin Red S staining, Oil Red O staining, and Alcian Blue staining, respectively, as validated in other MSCs models of avian origin [ 12 , 28 , 29 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the era of stem cell research, mesenchymal stem cells have been one of the key sources of cell-based therapies [51]. Different research groups identified, isolated, and compared the cellular morphology, surface markers, and differentiation abilities of MSCs derived from different sources [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. A lot of work has been performed to date to investigate the possible therapeutic effects of MSCs in different acute kidney injury models [16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are undifferentiated, self-renewable, non-hematopoietic adult stem cells of mesodermal origin [1]. These multipotent stem cells are broadly distributed in the body and can be relatively easily isolated from various tissues, such as bone marrow, umbilical cord blood, fat, muscle, periosteum, lung, testis, and dermis [2][3][4][5][6][7][8][9][10][11][12][13][14]. MSCs can differentiate into both mesenchymal and non-mesenchymal lineages, including differentiation toward adipocytes, chondrocytes, osteocytes, skeletal muscle cells, renal cells, and smooth muscle cells [9][10][11]15].…”
Section: Introductionmentioning
confidence: 99%
“…The cartilage tissue at the knee joints of the mice was isolated, cultured, and identified (Chan et al, 2018;Wang et al, 2018).…”
Section: Cell Transfection and Groupingmentioning
confidence: 99%